Distribution scenario of diseases in sugarcane germplasm at Kannur, Kerala - R Gopi; R Viswanathan; Chandran K; Nisha M; Mahendran B; Maya lekshmi; Gireesan P P (Journal of Sugarcane Research, 2021)
Survey and monitoring were done at monthly intervals during 2017-2019 for the occurrence of diseases in sugarcane germplasm at ICAR-Sugarcane Breeding Institute Institute Research Centre, Kannur. The study revealed the occurrence of ring spot in Saccharum species as well as in hybrid clones. Other diseases recorded were smut, rust, stalk rot, banded sclerotial disease and YLD. Among these diseases, only few clones such as IJ 76 552 and 28 NG 82 (Saccharum robustum), Co 844 and Co 62175 (Indian hybrids) were affected by smut. Rust is the common disease in the 32 hybrid clones and in four clones of S. spontaneum viz. IND 81-20, IND 81-74, IND 81-82 and IND 81-83. Only one S. officinarum clone IJ 76 501 was affected by rust till now. Stalk rot was observed mostly in S. officinarum clones and in few hybrid clones, respectively during 2017-2019. For the first time, leaf blight due to banded sclerotial disease was noticed in NG 77-145 of S. robustum, Agoul, Baroukha, Chin and Dark Pindaria of S. barberi and IS 76-168 of S. officinarum during 2019.